IOT based e – health care system - Chandrasekaran, R; Uzma Farheen, Syed; J.Hemalatha, R; Babu, Bincy; Arockiya Dhivya, Josephin; R Thamizhvani, T (International Journal of Engineering and Technology, 2018)
One of the most important technological evolutions of our time is CLOUD COMPUTING, which describes the web computing power to store and process the information. The evolution and advancements are swiftly increasing in remote monitoring and Telemedicine. This paper aims at transmitting the physiological parameters of the subject to the private cloud called Thing Speak, an IOT based Sensor monitoring system. The physiological parameters are sent to the cloud via ESP8266 (IOT device). The cloud computing helps the physician to be connected with the patient’s data and it is helpful in monitoring the patients at any time through internet.